What about the toxines analysis? new strategies for sensing applications using the chemistry of diazonium group - Gonzalez-Costas, Javier M. (2013)
Objectives: Typically, the Mouse BioAssay (MBA) is a method widely used in many laboratories for analysis of marine biotoxins together with chromatographic (UPLC-MS) one [1]. The MBA will be banned from December 2014 by the amending Regulation (EC) Nº 2074/2005 of 10th January 2011. Based on this regulation, new alternative methods are required for fast detection of biotoxins in aquatic environment and in shellfish samples. The aim of this research work is to design and to characterize an electrochemical (bio)sensor for rapid and sensitive detection of biotoxins.